Investigation of the technology effects of online travel media on virtual travel experience and behavioral intention. Issue 3 (24th March 2018) - Choi, Youngjoon; Hickerson, Benjamin; Lee, Jinsoo
ABSTRACT: This study investigates technology affordances of online travel media determining ways of presenting pictorial information and creating the spatial structure of a destination: modality and navigability. To examine the impacts of technology affordances on virtual travel experience, a 2 (modality: still pictures versus panoramic pictures) × 2 (navigability: absence versus presence) between-subjects experiment was conducted with 213 participants. This study found significant effects of modality and navigability on affective and cognitive dimensions of virtual travel experience. Scrutinizing the mediating role of virtual travel experience, the findings explain the psychological mechanism of how modality and navigability influence tourists' behavioral intention.